2009
DOI: 10.1038/onc.2009.148
|View full text |Cite
|
Sign up to set email alerts
|

Defective expression of polarity protein PAR-3 gene (PARD3) in esophageal squamous cell carcinoma

Abstract: The partition-defective 3 (PAR-3) protein is implicated in the formation of tight junctions at epithelial cell-cell contacts. We investigated DNA copy number aberrations in human esophageal squamous cell carcinoma (ESCC) cell lines using a high-density oligonucleotide microarray and found a homozygous deletion of PARD3 (the gene encoding PAR-3). Exogenous expression of PARD3 in ESCC cells lacking this gene enhanced the recruitment of zonula occludens 1 (ZO-1), a marker of tight junctions, to sites of cell-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 30 publications
5
82
0
Order By: Relevance
“…Genetic studies in Drosophila support the idea that loss of polarity is tumorigenic (Bilder, 2004;Bilder et al, 2000;Gateff, 1978). Moreover, Zen and colleagues found that the PARD3 gene is homozygously deleted in human esophageal squamous cell carcinoma cell lines (Zen et al, 2009). However, deletions and mutations of polarity genes are rare in human cancers, and the genes encoding aPKCζ, Par3, Dlg and Scribble can be amplified or overexpressed, suggesting they may also have pro-tumorigenic roles (Halaoui and McCaffrey, 2014;Huang and Muthuswamy, 2010;Lin et al, 2015;Rothenberg et al, 2010).…”
Section: Box 2 Cell Polarity In Birth Defects and Diseasementioning
confidence: 66%
“…Genetic studies in Drosophila support the idea that loss of polarity is tumorigenic (Bilder, 2004;Bilder et al, 2000;Gateff, 1978). Moreover, Zen and colleagues found that the PARD3 gene is homozygously deleted in human esophageal squamous cell carcinoma cell lines (Zen et al, 2009). However, deletions and mutations of polarity genes are rare in human cancers, and the genes encoding aPKCζ, Par3, Dlg and Scribble can be amplified or overexpressed, suggesting they may also have pro-tumorigenic roles (Halaoui and McCaffrey, 2014;Huang and Muthuswamy, 2010;Lin et al, 2015;Rothenberg et al, 2010).…”
Section: Box 2 Cell Polarity In Birth Defects and Diseasementioning
confidence: 66%
“…Recently, loss or reduction of PAR-3 expression was described in esophageal squamous cell carcinoma and in breast tumors 17,28 and only one study reported PARD3 amplification in a radiation-transformed neoplastic retinal pigment epithelial cell line. 29 In our work, we identified an overexpression of PAR-3 associated with an alteration of the localization of the protein both in the R-180 cell line and in the original tumor.…”
Section: Discussionmentioning
confidence: 99%
“…10 For instance, homozygous deletion of PARD3 (the gene that encodes the PAR-3 protein) has been detected in primary esophageal squamous cell carcinomas in which decreased PARD3 mRNA levels are observed in more than two thirds of cases. 17 However, PAR-3 deregulation in ccRCC has never been investigated and its prognostic value is unknown. In this work, we conducted a genomic study using two primary cell lines derived from surgical ccRCC specimens from two patients with different survival rates but with similar clinical and histological features at diagnosis.…”
mentioning
confidence: 99%
“…Loss of polarity genes in Drosophila can also synergize with oncogenes to generate tumors that invade and metastasize aggressively (10,42,43). Although Pard3 is mutated or its expression is altered in several human cancers (44,45), experimental confirmation for PAR3 as a mammalian tumor suppressor has only recently been reported (14 -16). The molecular mechanisms underlying this tumor suppressor function remain partially obscure.…”
Section: Discussionmentioning
confidence: 99%